Therapeutic diet for primary care - Amrita Ghosh; Swapan Kumar Paul; Ranabir Pal; Shrayan Pal (Al Ameen Medical College, 2019)
Background: Therapeutic diet is an important concept in health and disease, and should be taught at all levels ranging from healthcare providers, stakeholders, and to healthcare seekers equally, without any prejudice, which is not done at present; so this review is applicable for the current scenario and will help sensitise readers regarding this crucial issue. Objective: A narrative review was taken up, which was very much required for a concerted all round application for a fruitful teaching-learning. Methods: Thirty-six research studies were identified from 73 potentially relevant articles. Studies and data bases were selected on, firstly, all therapeutic nutritional plans and corresponding diets in disease among published literature were sketchily searched, secondly, 'Therapeutic diets' impacting diagnosis and prognosis in different morbidities were identified, thirdly, published reports from apex bodies of global importance like World Health Organization (WHO), Centre for Disease Control (CDC), Atlanta USA and others were given due weightage for their multi-authored authenticity. Results: In spite of substantial growth in healthcare, the quality of research on therapeutic diets is sparse and often restricted to discharge from hospital and not reported in structured form without any research on compliance on dietary advices. In this review, various diets in different diseases and health conditions have been discussed in detail by especially taking up their pros and cons for the best possible outcome. Conclusions: In the current scenario we felt that nutrition is an orphan chapter in the healthcare field and we require more research about therapeutic diets as it is very useful in daily medical practice from primary level to tertiary care levels for the improvement in clinical approach and treatment in patients with diverse diseases.